A Case of Metastatic CNS Melanoma of Unknown Primary Presenting with Seizures - Viva Nguyen; Samar Aboulenain; Shawn Mohammed; Sahyli Perez Parra (Case Reports in Medicine)
Seizures are a common occurrence. The goal of evaluating a seizure is to identify the etiology and to determine the likelihood of recurrence as well as guide management. We present a unique presentation of a 47-year-old female that presented with late onset seizures admitted due to status epilepticus. Brain magnetic resonance indicated diffuse supratentorial hemorrhagic lesions. Neurological workup including brain vessel imaging, CT chest, abdomen, and pelvis as well as CSF and serological workup for vasculitis failed to demonstrate the cause of her brain lesions. Ultimately, a brain biopsy showed metastatic melanoma of unknown primary origin.